Malaysia’s Aspirations To Be An International Islamic Financial Centre: A Central Banker’s Perspective On The Role And Viability Of Malaysia International Islamic financial centre (mifc) using stakeholder theory" - Balakrishnan, Inbhashelvi (2010)
There is a global shift taking place in the environment that is altering the global economy. With that aspect taking shape, there will be the need to develop and strengthened strategic financial linkages and development of new areas of financial growth. These developments will be come an interesting and important feature in this changing environment. One of the new areas of new growth and development is Islamic finance. At the early stages, the development of Islamic finance was very much domestic centred. But in the recent years, there has been a lot growth and developments in Islamic finance all over the world. Islamic finance is deemed to be as one of the leading industry in the banking and financial sector. Malaysia is very much keen to be part of this new growth development. The purpose of this study is to bring the aspiration and experience of Malaysia in developing the Islamic financial system and the establishment of the Malaysia International Islamic Financial Center (MIFC). The focus would be on what is MIFC and how MIFC has been developed to promote Islamic finance in Malaysia and how an arrangement like this entity could be viable to Malaysia. This paper then concludes by discussing the challenges of having an entity such as MIFC and the way forward for the long term. This study would be using Stakeholder theory to understand the role of MIFC in promoting Islamic finance. For this study the methodology used, was semi structured questionnaire and as well as gathering information from various sources such as journals, presentations and speeches by Governor of Bank Negara Malaysia (Central Bank of Malaysia) and analyzing these papers accordingly to bring out the possible implications to Malaysia. However since MIFC has been only established in the last 4 years, the majority of the data collected and analyzed was based on the interviews that was done to get a better understanding on the viability of MIFC. The results of this study would bring an interesting perspective to other countries wanting to start a similar initiative and the possible outcomes and challenges that would be encountered along the way.